2013
DOI: 10.2215/cjn.07780812
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Race and Geographic Area and Quality-of-Care Indicators in Patients Approaching ESRD

Abstract: Background and objectives Pre-ESRD care is an important predictor of outcomes in patients undergoing longterm dialysis. This study examined the extent of variation in receiving pre-ESRD care and black-white disparities across urban and rural counties.Design, setting, participants, & measurements Participants were 404,622 non-Hispanic white and black patients aged .18 years who began dialysis between 2005 and 2010 and resided in 3076 counties from the U.S. Renal Data System. The counties were grouped into large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 33 publications
(35 reference statements)
3
53
1
Order By: Relevance
“…For example, a recent national analysis of all patients with ESRD in the USRDS revealed the lower rates of initiating dialysis with an arteriovenous fistula for black and Hispanic patients than whites, but the analysis did not assess contextual factors jointly with the patient factors (35). The few studies that examined contextual factors found some particular aspects of residential areas associated with the lower likelihood of patients having received pre-ESRD care, including residential areas with larger proportions of black residents (23), counties with greater poverty (25), large metropolitan or rural counties (24), or states with more stringent Medicaid coverage (36). Another study found substantial variation in pre-ESRD care across treatment centers (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent national analysis of all patients with ESRD in the USRDS revealed the lower rates of initiating dialysis with an arteriovenous fistula for black and Hispanic patients than whites, but the analysis did not assess contextual factors jointly with the patient factors (35). The few studies that examined contextual factors found some particular aspects of residential areas associated with the lower likelihood of patients having received pre-ESRD care, including residential areas with larger proportions of black residents (23), counties with greater poverty (25), large metropolitan or rural counties (24), or states with more stringent Medicaid coverage (36). Another study found substantial variation in pre-ESRD care across treatment centers (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although the receipt of nephrologist care is influenced by individual as well as contextual factors such as those related to residence, prior studies have mostly examined individual factors (12,(19)(20)(21), or the few studies that examined contextual factors have generally examined them separately (22)(23)(24) or were limited to certain regional areas (15,25). An important knowledge gap exists regarding broad regional (e.g., state-level) differences in the utilization of nephrologist care among patients with CKD stages 4-5.…”
Section: Introductionmentioning
confidence: 99%
“…However, anemia in a majority of patients with nondialysis CKD (NDD-CKD) stages 3b-5a is not treated and often delayed because of late nephrology referral and ESA reimbursement limitations (9). Between 2005 and 2010, only 28% of patients with CKD in the United States received ESA before dialysis initiation (10).…”
Section: Introductionmentioning
confidence: 99%
“…There are also racial and ethnic differences in the processes of care, including dialysis dose (6,7), anemia treatment (8,9), hemodialysis vascular access (10)(11)(12)(13), and pre-ESRD clinical care (12,14). Prior studies examining hospitalization in dialysis patients usually used race, among others, as an explanatory factor or control variable (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%